DESIGN EXPLORATION OF MICROCATHETER TIP GEOMETRY FOR SEGMENTAL ADRENAL VENOUS SAMPLING USING COMPUTATIONAL FLUID DYNAMICS - Muliany, Johanna
In 2013, WHO reported that cardiovascular disease was a major cause of global mortality, contributing to 1/3 of its total, where 45% of said cases are caused by hypertension. One of the causes of hypertension is aldosterone-producing adenoma (APA), identified by the presence of tumor in the adrenal glands. Therefore, a proper diagnosis of APA is necessary so that the patient can receive the appropriate medical treatment. Currently, the gold standard in the detection of APA in the body is the adrenal venous sampling (AVS) procedure. The most recent development of the AVS procedure is the S-AVS procedure, in which the blood sample is taken at the first branch of the central adrenal vein. Practically, there are several issues in the sampling process that are generally thought to be caused by venous constriction. To overcome this, the latest development in S-AVS is the use of a split-tip microcatheter, namely a microcatheter with a notch at one end. In practice, the microcatheter is considered capable of increasing the success of the sampling process. There are several studies which report that the use of a split-tip microcatheter reduces venous constriction. However, there is a need for a physical explanation of the effect of the use and design of the split-tip microcatheter in the S-AVS procedure. In this final project, an exploration of the split-tip microcatheter design is performed as an effort to explain its effects in the S-AVS procedure. Exploration of the microcatheter’s design variables, namely the amount and depth of the notches, was carried out in silico through computational fluid dynamics (CFD) simulations and metamodel construction of the system response. In the CFD simulation, model validation is carried out through the mesh independence test. The response metamodel construction was carried out using the Kriging regression method, so that the response of venous constriction with regards to the number and depth of notches could be described holistically.